A Bibliometric Analysis of Employee Advocacy and its Role in Enhancing Brand Loyalty - Fitra Hasri Rosandi; Imam Bustomi; Gustian Djuanda (Westscience Press, 2024)
This bibliometric analysis explores the intricate relationship between employee advocacy and brand loyalty, providing insights into how internal stakeholder engagement impacts consumer perceptions and brand success. Utilizing a systematic review of academic literature from more than past two decades, the study highlights the pivotal role of employees as brand ambassadors and the subsequent effect on customer trust and loyalty. Through an examination of key studies, including works by Aaker (2011) and Chaudhuri & Holbrook (2001), the research underscores the significance of aligning employee experiences with external brand promises to enhance brand equity. The findings suggest that effective employee advocacy programs are crucial for fostering brand loyalty, particularly in environments where competition and consumer expectations are continuously evolving. Strategic implications are discussed, emphasizing the need for organizations to adapt their employee advocacy efforts in response to dynamic market conditions and evolving technological landscapes.